2021
DOI: 10.3390/app11051995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Keratin/Bacterial Cellulose Based Scaffolds as Potential Burned Wound Dressing

Abstract: The study presents the preparation and characterization of new scaffolds based on bacterial cellulose and keratin hydrogel which were seeded with adipose stem cells. The bacterial cellulose was obtained by developing an Acetobacter xylinum culture and was visualized using SEM (scanning electron microscopy) and elementally determined through EDAX (dispersive X-ray analysis) tests. Keratin species (β–keratose and γ-keratose) was extracted by hydrolytic degradation from non-dyed human hair. SEM, EDAX and conducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…1 In the recent years, the focus has been changed to the development of biologically active materials which are able to regulate interactions with cells as well as to control their functions. 2,3 Currently, there are many studies dealing with preparation of special biofunctional materials for engineering of different tissues, [4][5][6] including bone tissue. 7,8 Among various materials for bone defect substitution, the resorbable osteoconductive scaffolds, which are able to induce an efficient formation of the natural autogenous bone tissue, are of major scientific interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the recent years, the focus has been changed to the development of biologically active materials which are able to regulate interactions with cells as well as to control their functions. 2,3 Currently, there are many studies dealing with preparation of special biofunctional materials for engineering of different tissues, [4][5][6] including bone tissue. 7,8 Among various materials for bone defect substitution, the resorbable osteoconductive scaffolds, which are able to induce an efficient formation of the natural autogenous bone tissue, are of major scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the focus has been changed to the development of biologically active materials which are able to regulate interactions with cells as well as to control their functions 2,3 . Currently, there are many studies dealing with preparation of special biofunctional materials for engineering of different tissues, 4–6 including bone tissue 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…The in vitro and in vivo test results show that the reconstruction of damaged structures is much faster than that with bacterial cellulose. 19 All of these research results demonstrated that the incorporation of keratin improves the ability for cell attachment. However, in all of these previous works, the used keratin was extracted by the Shindai extraction method, 20 where the keratin dissolution and extraction take almost 5 days.…”
Section: Introductionmentioning
confidence: 92%
“… BC-based materials are synthesized by aerobic bacteria as extremely pure natural exopolysaccharides . These materials with nontoxicity, attractive mechanical features required for scaffolds (strength and moldability) in dry/wet conditions, inherent biocompatibility, and good light transmittance as well as the fascinating physical characteristics (e.g., purity, crystallinity, and wettability) have been widely explored for biosensing, drug/gene delivery, wound healing, and TE purposes. , Compared to plant-derived cellulose, BC has some advantages including higher crystallinity, purity, tensile properties, Young’s modulus, and value of degree of polymerization . However, there are still some challenges and disadvantages to apply BC in clinical stages pertaining to their biocompatibility and biodegradability.…”
Section: Polysaccharide-based Biomaterials For Cardiovascular Tementioning
confidence: 99%